2017
DOI: 10.5152/eurjther.2016.02020
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of knowledge level of married men about sexually transmitted diseases

Abstract: ÖZAmaç: Bu çalışmada cinsel yolla bulaşan hastalıkların (CYBH) yayılmasında önemli role sahip ve aynı zamanda risk grubunun büyük kısmını oluşturan evli erkeklerin CYBH'ler ile ilgili bilgi seviyeleri ve bilgi seviyelerinin sosyo-demografik faktörlere göre değişiklik göste-rip göstermediği araştırıldı.Yöntemler: Araştırmaya 21-71 yaş arası 200 evli erkek dahil edildi. Veriler araştırmacılar tarafından literatür doğrultusunda oluşturulan 12 adet sosyo demografik, 15 adet CYBH ve 45 adet CYBH bulaşma yollarına i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…men aged between 21-71 years, it was observed that the majority of them had a low level of knowledge about STDs (28).…”
Section: Discussionmentioning
confidence: 99%
“…men aged between 21-71 years, it was observed that the majority of them had a low level of knowledge about STDs (28).…”
Section: Discussionmentioning
confidence: 99%